ENGLISH TEACHERS' PERCEPTION ON PRACTICALITY AND USEFULNESS OF ONLINE LEARNING DURING THE COVID-19 PANDEMIC AT TWO JUNIOR HIGH SCHOOLS - Rahmatika, Yulia (Langue (Journal of Language and Education), 2022)
Since March 2020, the coronavirus disease, also known as COVID-19 has become a global pandemic. According to UNESCO, schools were closed in about 100 countries due to a public health emergency, including Indonesia. The condition forced teachers to make the transition from face-to-face learning to online learning. This study aims to determine the perceptions of EFL teachers about the practicality and usefulness of online learning at two junior high schools in Batang Hari regency, Jambi province. The researcher used a descriptive qualitative design and employed a semi-structured interview to collect the data. The subjects of this research are two English teachers at two Junior High Schools in Batang Hari regency. The findings showed that in terms of practicality, the teachers consider online learning was more practical, flexible, and effecient during online learning. In terms of usefulness, the teachers felt that the use of technology increased their knowledge of using technology, especially on an online platform.